Supernumerary Molars and Wisdom Tooth Shape Alterations in Patients with Neurofibromatosis Type 1 - Reinhard E. Friedrich; Anika Reul (Stilus Optimus, 2017)
Objectives: The purpose of the present study was the systematic investigation of numerical and morphological aberrations of teeth in the wisdom teeth region in neurofibromatosis type 1 patients. Material and Methods: The panoramic radiographs of 179 patients were analysed for supernumerary molars and dysplastic wisdom teeth with special reference to facial tumour type. The results were compared to radiographic findings obtained in panoramic radiographs of age- and sex-matched controls. Results: The total number of dysplastic or supernumerary molars was 21 (17 individuals, 4.75%) and predominantly a finding of the maxilla (maxilla: 15, mandible: 1, maxilla and mandible: 1). Differences of dental findings between neurofibromatosis type 1 (NF1) patients (n = 15) and the control group (n = 2) were statistically significant (P < 0.01). All individuals with supernumerary molars were diagnosed as being affected with NF1. This difference achieved statistical significance when it was considered that the event may occur at least once per quadrant, and thus the individual potentially needs to be considered four times (P = 0.0038). Conclusions: This investigation revealed that supernumerary molars and aberrations in wisdom tooth form are more common in patients than in age- and sex-matched controls. There is no association between these findings and a specific feature of the disease, id est facial manifestation of a trigeminal nerve sheath tumour (plexiform neurofibroma). The cause of this phenomenon is unknown. A review of these dental findings on other neurofibromatosis type 1 study groups should be attempted.